Mdind mapping. (Economist, 2023)
The article reports on a study published in "Science," in which researchers mapped the brain of a fruit-fly larva to determine how it can sense its environment, avoid predators, and search for food. In the project, the scientists charted the locations of the neurons and synapses of the larva's brain. Also cited is the connectome study programme proposed by neuroscientist Marta Zlatic.